REKONSILIASI KOSMOLOGIS Antara Teorema Penciptaan dan Teori Evolusi - Gunawan, Leo Agung Srie (LOGOS, 2020)
The problem of the universe having a great mystery encloses the big question about its origin. To answer the origin of universe, generally, there are two approaches, namely faith and science. The main question has to be replied: â€œWhat do the differences and the similarity of them?â€ The approach of faith bases on the inquiry of â€œwho causes the existence of the universeâ€. This approach states that the origin of universe was created by God and hence, it was formed by God from a nothingness (creatio ex nihilo). This is known as the theorem of creation. Furthermore, the scientific approach is grounded on the research of â€œhow the universe was formed in the beginningâ€. This oncoming being explained by the Big Bang Theory, which is continued by the Big Crunch Theory, asserts that the origin of universe came from the prime matter which exploded incredibly in a such a way that the formation process of the universe took place (the singularity). This is well-known as the theory of evolution (the cosmological evolution). In conclusion, the scientific approach explaining the process of creation and the faith one answering the actor of it are complementary.